An experimental investigation of a novel iron chelating protoporphyrin IX prodrug for the enhancement of photodynamic therapy. Issue 5 (31st March 2018) - Anayo, Lizette; Magnussen, Anette; Perry, Alexis; Wood, Mark; Curnow, Alison
Abstract : Objectives: Non‐melanoma skin cancers are the most frequently occurring type of cancer worldwide. They can be effectively treated using topical dermatological photodynamic therapy (PDT) employing protoporphyrin IX (PpIX) as the active photosensitising agent as long as the disease remains superficial. Novel iron chelating agents are being investigated to enhance the effectiveness and extend the applications of this treatment modality, as limiting free iron increases the accumulation of PpIX available for light activation and thus cell kill. Methods: Human lung fibroblasts (MRC‐5) and epithelial squamous carcinoma (A431) cells were treated with PpIX precursors (aminolaevulinic acid [ALA] or methyl‐aminolevulinate [MAL]) with or without the separate hydroxypyridinone iron chelating agent (CP94) or alternatively, the new combined iron chelator and PpIX producing agent, AP2‐18. PpIX fluorescence was monitored hourly for 6 hours prior to irradiation. PDT effectiveness was then assessed the following day using the lactate dehydrogenase and neutral red assays. Results: Generally, iron chelation achieved via CP94 or AP2‐18 administration significantly increased PpIX fluorescence. ALA was more effective as a PpIX‐prodrug than MAL in A431 cells, corresponding with the lower PpIX accumulation observed with the latter congener in this cell type. Addition of either iron chelating agent consistently increased PpIX accumulation but did not always convey an extra beneficial effect on PpIX‐PDT cell kill when using the already highly effective higher dose of ALA. However, these adjuvants were highly beneficial in the skin cancer cells when compared with MAL administration alone. AP2‐18 was also at least as effective as CP94 + ALA/MAL co‐administration throughout and significantly better than CP94 supplementation at increasing PpIX fluorescence in MRC5 cells as well as at lower doses where PpIX accumulation was observed to be more limited. Conclusions: PpIX fluorescence levels, as well as PDT cell kill effects on irradiation can be significantly increased by pyridinone iron chelation, either via the addition of CP94 to the administration of a PpIX precursor or alternatively via the newly synthesized combined PpIX prodrug and siderophore, AP2‐18. The effect of the latter compound appears to be at least equivalent to, if not better than, the separate administration of its constituent parts, particularly when employing MAL to destroy skin cancer cells. AP2‐18 therefore warrants further detailed analysis, as it may have the potential to improve dermatological PDT outcomes in applications currently requiring enhancement. Lasers Surg. Med. 50:552–565, 2018. © 2018 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals, Inc.